Merespon Covid-19: Manajemen Dakwah Masjid Raya Darussalam Palangkaraya masa Pandemi - Beni Prakoso; Harles Anwar; mualimin mualimin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2021)
ABSTRACTThis study aims at analyzing the da'wa management of the grand mosque. This qualitative research takes a phenomenological approach. Specifically Fred R. David’s strategic management model used to analyze the management of da'wah at the Darussalam Grand Mosque. There are three aspects of management that are the focus of this study, namely formulation, implementation, and evaluation of da'wah. The data was collected through observation, interviews and documentary studies. The results revealed that there were three important points in the mosque's da'wa management. Firstly, the mosque's managerial team made an adaptation by reformulating their programs for today's pandemic. Secondly, the implementation of the da'wah programs is not only intended to increasing the devotion of the congregation, but also the literacy and habituation of the health protocols both with verbal and non-verbal communication. Thirdly, the evaluation is done continuously so that the implementation is in accordance with the formulated targets. It is concluded that the da'wa management of da'wah at the grand mosque during the Covid-19 pandemic is not only about  increasing the ritual piety but also creating social kindness and humanitarian care through applying the health protocols and Covid-19 literacy. The implication of the results of this study is as a model for the management of mosque da'wah in responding and adapting to various force majeure conditions.Keywords : Da’wa Management; Covid-19; Pandemic; The Darussalam Grand Mosque